Pengaruh Belanja Daerah, Jumlah Penduduk, Dan Konsumsi Terhadap Pertumbuhan Ekonomi Di Provinsi Kalimantan Barat - B01112059, SUSANTI B01112059 (Jurnal Curvanomic, 2016)
Economic growth indicates the success of economic development in a country.Economic development is an effort made to improve the welfare of societymarked by the increase of production of goods and services. This research aims toexamine and analyze the effect of regional expenditure, number of population, andconsumption on economic growth in West Kalimantan Province. This researchused a quantitative method with a multiple linear regression model. Researchfindings show that the regional expenditure had a positive and significant effecton economic growth in West Kalimantan province because the regionalexpenditure measured from routine expenditure had a quite important role andfunction to support the goals of development, Number of population had apositive insignificant effect on economic growth in West Kalimantan Provincebecause the increase in population is not accompanied by the quality of humanresources, consumption had a negative insignificant effect on economic growth inWest Kalimantan province because consumption is decreasing.Keywords: Regional Expenditure, Number of Population, Consumption,Economic Growth.